Association of Monocyte Chemotactic Protein-1 and Dickkopf-1 with Body Composition and Physical Performance in Community-Dwelling Older Adults in Singapore. - Afandy, Nathania Octaviani (Hylonome Publications, 2021)
10.22540/JFSF-06-025